Singapore’s judicial system (experience in the 2020 pandemic) (Journal of actual problems of jurisprudence, 2021)
The task of constantly improving the efficiency of justice continues to be relevant due to its versatility and the growing demand of society. In order to continue this discussion, the article analyzes the judicial system of Singapore through the prism of its judicial system and judicial proceedings. The purpose of the work is to analyze the practical solutions of the studied justice, to highlight the positive and negative experience. The scientific and practical significance of the study lies in the fact that there is a positive practice of increasing the level of accessibility and openness of justice. As a result, it seems possible to implement the norms of foreign law due to the proximity of the emerging needs of judicial systems, both in Russia and in Kazakhstan. Methodological basis: formal legal method, synchronous and diachronic methods, as well as general scientific methods of cognition. A brief overview of the Singapore justice system, including the experience of implementing electronic technologies in this system, is given. The author shows that the introduction of these technologies and reasonable deterimental some elements of the trial allows to reduce the bureaucratic and material costs, as well as more efficiently and safely in a pandemic 2020 use human resources of the court and other persons involved in the case.Keywords: electronic court, automation of legal proceedings, accessibility of justice, internet. References: [1] Alenov M.A., Implementation of e-justice in Kazakhstan: regulatory framework and prospects // KAZGUU University. – Astana: Law and State, 2013. No. 3 (60). S. 71-73.[2] Cornie Ng. Integrated Electronic Litigation System (iELS) for the Singapore Ludiciary. URL: http: // mstreamlegal.com/ uploads / upload_ legal_ research_ center / lntegrated% 20Litigation% 20system.pdf.[3] Zhuikov V., Borisova E., Golovko L., Bonner A., Yarkov V., Afanasyev S., Pashin S., Patsatsiya M., Tai Yu., Smolnikov D. Reform of the judicial system in Russia: a new stage // Zakon. – M .: Zakon, 2016, No. 11 S. 20-34.[4] Zorkin V.D. The letter and spirit of the Constitution // Rossiyskaya Gazeta. – M .: Rossiyskaya Gazeta, 2018. No. 7689 (226) // SPS ConsultantPlus.[5] In the Supreme Court of the Republic of Singapore Registrar’s Circular No. 3 of 2020 (Mar. 27, 2020) (Supreme Court Circular), https://perma.cc/K5CE-9YW4.[6] Legislation, CRT, https://perma.cc/2XMY-P6D8.[7] Malik, Walled Haider. Judiciary-Led Reforms in Singapore: framework, strategies and lessons. The World Bank, 2007. P. 53.[8] Media Release, Supreme Court, State Courts and Family Justice Courts to Hear Only Essential and Urgent Matters from 7 April to 4 May 2020 (Apr. 5, 2020), https://perma.cc/8WE5-RVQ4.[9] Message from Chief Justice Sundaresh Menon, The Singapore Judiciary’s Response to COVID-19 (Mar. 26, 2020), https:// perma.cc/WA7T-DBHN.[10] Momotov V.V. Justice and expediency in the Anglo-American and continental-European legal systems: problem statement // Russian justice. 2017.No. 12.P. 16-24.[11] Lim Seng Siew. The Role of Service Bureaux in EFS. URL: http: // www.lawgazette.com.sg/ 2000-2 / Feb00-20.htm.[12] Reshetnyak V.I. Information technologies in the judicial system of Singapore // Information law. 2012. N 2.P. 21 – 24 // SPS ConsultantPlus.[13] Rogov I. I. Reforming according to the principle of the rule of law // Legal newspaper. 2016. No. 130.[14] Singapore Judicial System, Supreme Court of Singapore (last updated June 7, 2019), https://perma.cc/Z2SX- UFCL.[15] Tan Siong Thye. Senior District Judge Subordinate Courts of Singapore. Current reforms in Asean countries – lessons and experiences. The Singapore’s experience. URL: http: // www.aseanlawassociation.org/ 10GAdocs /. URL: http:// app.supremecourt.gov.sg.[16] Walker J., Watson G.D. New Technologies and the Civil Litigation Process. Common Law General Report. Osgoode Hall Law School York University, Toronto (Canada) http: // research.osgoode.yorku.ca/ iapl2007.[17] Wong Peck. eJustice-Transforming The Justice System. URL: http:// www.aija.org.au/ Law&Tech%2008/ Papers/.[18] Woolf H.K. Access to justice – Final Report to the Lord Chancellor on the civil justice system in England and Wales. London, 1996 https://www.goodreads.com/book/show/1632182.Access_to_Justice.